2014
DOI: 10.1016/j.clnu.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Protein intake and exercise for optimal muscle function with aging: Recommendations from the ESPEN Expert Group

Abstract: The aging process is associated with gradual and progressive loss of muscle mass along with lowered strength and physical endurance. This condition, sarcopenia, has been widely observed with aging in sedentary adults. Regular aerobic and resistance exercise programs have been shown to counteract most aspects of sarcopenia. In addition, good nutrition, especially adequate protein and energy intake, can help limit and treat age-related declines in muscle mass, strength, and functional abilities. Protein nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
1,038
9
62

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,247 publications
(1,152 citation statements)
references
References 89 publications
(94 reference statements)
43
1,038
9
62
Order By: Relevance
“…Immobilisation induces resistance of muscle to anabolic stimulation (66) . Age-related muscle loss is primarily due to decreased postprandial muscle protein synthesis rather than increased breakdown (11,65) . Inactivity induces anabolic resistance (65) , and a reduction of physical activity for 2 weeks was shown to induce anabolic resistance in older adults, with decreased postprandial protein synthesis, decreased insulin sensitivity, and decreases in leg muscle mass (67) .…”
Section: Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Immobilisation induces resistance of muscle to anabolic stimulation (66) . Age-related muscle loss is primarily due to decreased postprandial muscle protein synthesis rather than increased breakdown (11,65) . Inactivity induces anabolic resistance (65) , and a reduction of physical activity for 2 weeks was shown to induce anabolic resistance in older adults, with decreased postprandial protein synthesis, decreased insulin sensitivity, and decreases in leg muscle mass (67) .…”
Section: Physical Activitymentioning
confidence: 99%
“…The relationship between age-related loss of muscle mass and strength is often independent of body mass. When muscle mass is lost but fat mass is elevated the state is called sarcopenic obesity and a suggested definition is 'deficiency of skeletal muscle relative to fat tissue' (11,12) . Loss of muscle mass and function can be caused by multiple mechanisms.…”
Section: Frailty Sarcopenia and Cachexiamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the need for more dietary protein with ageing is in part due to a compromised ability to efficiently utilize amino acids for MPS, resulting in a blunted muscle protein synthetic response to an anabolic stimuli, a phenomenon termed anabolic resistance [105,106]. As of consequence, evidence based recommendations for protein intake in older adults have recently been published [107,108]. Despite the potential role of dietary protein in relation to muscle preservation and function, an important determinant of MPS is not only an adequate intake of dietary protein but also the signalling of anabolic molecules [109].…”
Section: Underlying Mechanisms Underpinning the Potential Benefits Ofmentioning
confidence: 99%
“…My experience matches the dietitians in the survey who described eating as a teaching opportunity, because boiled peanuts, pretzels, extra-large colas, and nacho cheese corn chips make great food for discussion about healthy food choices. Most studies showing benefit of feeding on dialysis have used nutritional supplements, but studies in other settings suggest that mixed meals of similar composition could be equally beneficial (20,21). Benner et al (19) developed sensible suggestions (shown in the supplemental material in ref.…”
mentioning
confidence: 99%